Moderating effect of emotional intelligence and social support on relationship between work-family conflict, psychological well-being and job performance - Zainal, Nurhafizah (2018)
Service industry has become the major player in Malaysian economy. The heavy workloads in service companies in order to cater the needs of the people have led to work-family conflict among employees. Work and family represent important life roles for most employees. However, many employees are grappling with conflicts experienced in meeting the demands and responsibilities of these two roles. Work-family conflict consists of two domains namely work interference family (WIF) and family interference work (FIW). Employees experienced WIF and FIW when demands of one role interfere with participation or performance of the other role. The main objective in this study is to examine the moderating role of emotional intelligence and social support on the relationship between work-family conflict, psychological well-being, and job performance among employees in Malaysian service industry. Emotional intelligence and social support were chosen as moderating variables in this study due to limited studies found in addressing the effect of these variables on work-family conflict. Furthermore, emotional intelligence may act as a buffer on negative effect of work-family conflict. Meanwhile, social support may function as maladaptive coping strategies when work and family roles collide. The present study adopted Role Theory and Conservation of Resource Theory as the underpinning theories for its proposed conceptual framework. Based on the positivist paradigm, this study employed a quantitative method through questionnaires distribution. The data was obtained from the service employees’ sample (n = 377) in the area of Selangor and Klang Valley, Malaysia.The Structural Equation Modeling (SEM) analysis results suggested that nine out of twelve proposed hypotheses were supported. The study found that work-family conflict does not contribute significantly to employee’s psychological well-being. However, work-family conflict contributes significantly to employee’s job performance. In addition, the study found that emotional intelligence and social support play a significant role in moderating the relationship between work-family conflict, employee’s psychological well-being and job performance. The results of this study are deemed important in work-family conflict literature, providing new perspectives to the employees in service companies on ways to manage multiple roles in their daily lives. Apart from that, this study has important implications for service companies. A good understanding on how work-family conflict affecting employee’s psychological well-being and job performance is expected to help the service companies in managing their employees.